Consensus Based Indian Guidelines for the Management of Pemphigus Vulgaris and Pemphigus Foliaceous - Dipankar De; Hitaishi Mehta; Shikha Shah; Kidangazhiathmana Ajithkumar; Shyamanta Barua; Laxmisha Chandrashekar; Manas Chatterjee; Vishal Gupta; Sujay Khandpur; Geeti Khullar; Seetharam Anjaneyulu Kolalapudi; Sheetanshu Kumar; et al. (Indian Dermatology Online Journal)
Pemphigus is an autoimmune blistering disorder characterized by the presence of intraepidermal blisters and erosions, primarily affecting the mucosa and/or skin. There are no established Indian guidelines for the management of pemphigus, and Western guidelines cannot be directly applied due to differences in clinicodemographic profiles, comorbidities, and resource limitations. These guidelines aim to provide Indian dermatologists with evidence-based and consensus-driven recommendations for the management of pemphigus vulgaris (PV) and pemphigus foliaceous (PF), taking into account the unique challenges posed by the Indian healthcare setting. The guidelines focus on the comprehensive management of PV and PF, addressing diagnosis, treatment, monitoring, and follow-up. It is intended for dermatologists working in both outpatient and inpatient settings across India. The first draft of the guidelines was prepared by the writing group and then reviewed by 19 national experts in pemphigus management, including inputs from allied specialties. Areas with limited evidence or anticipated variation in recommendations were subjected to rounds of voting, with responses categorized as “strongly agree,” “agree,” “neutral,” “disagree,” or “strongly disagree.” Suggestions were incorporated, and statements were revised until a mean agreement score of 4 or higher was reached across 16 key areas after four voting rounds. These guidelines offer a structured approach to managing pemphigus in India, addressing the need for region-specific recommendations that account for unique challenges such as resource constraints and specific comorbidities in Indian patients. They serve as a valuable resource for dermatologists treating pemphigus in a range of clinical settings.